Heteronormativity and the victimization of bisexual and pansexual women: an empirical test of norm-centered stigma theory - Worthen, Meredith Gwynne Fair (Critical criminology, 2022)
Recent research suggests that bisexual women may be at high risk for victimization due to their non-monosexual identities, yet it is unclear whether pansexual women, who also have non-monosexual identities, may be at high risk for victimization as well. In the current study, data from a sample of adults in the United States, between the ages of eighteen and sixty-four and stratified by census categories of age, gender, race/ethnicity and census region collected from lesbian, gay, bisexual and transgender (LGBT) online panelists (n = 1559), were utilized to investigate bisexual (n = 358) and pansexual (n = 45) women’s victimization through a test of Norm-Centered Stigma Theory with a theoretical focus on heteronormativity and intersecting experiences with social power (gender and sexuality) (Worthen 2020). Three notable findings emerged. First, pansexual women experienced higher levels of harassment when compared to bisexual women. Second, both being pansexual and being a pansexual woman significantly increased the odds of enduring violence and harassment. Third, being a bisexual woman decreased the odds of experiencing violence and was not statistically significantly related to harassment. Overall, results suggest that pansexual women may have especially unique experiences that put them at risk for victimization and demonstrate the importance of specifically examining pansexual women’s experiences as separate from others. A discussion of the contributions and limitations of quantitative analyses in critical criminology, in general, and queer criminology, in particular, is also provided. Because this study is the first to highlight the intersecting experiences of pansexual women and their elevated risk of violence and harassment, the findings provide a much-needed first step into working toward developing a deeper understanding of pansexual people’s victimization. In addition, the results demonstrate the need for future research across multiple methods of investigation, including qualitative, quantitative, and mixed-methods approaches to best understand these relationships.